Defining the Species Micromonospora saelicesensis and Micromonospora noduli Under the Framework of Genomics - Riesco, Raúl; Carro, Lorena; Román-Ponce, Brenda; Prieto, Carlos; Blom, Jochen; Klenk, Hans-Peter; Normand, Philippe; Trujillo, Martha E. (Frontiers in Microbiology, 2018)
The type isolates of species Micromonospora saelicesensis and Micromonospora noduli are Gram-stain positive actinobacteria that were originally isolated from nitrogen fixing nodules of the legumes Lupinus angustifolius and Pisum sativum, respectively. These two species are very closely related and questions arise as to whether they should be merged into a single species. To better delineate the relationship of M. saelicesensis and M. noduli, ten strains isolated from plant tissue (nodules and leaves) and identified by their 16S rRNA gene sequences as either M. saelicensesis or M. noduli, based on a cut-off value of >99.5% were selected for whole-genome sequencing and compared with the type strains of M. saelicesensis Lupac 09T and M. noduli GUI43T using overall genome relatedness indices (OGRI) which included ANI, OrthoANI and digital DNA-DNA hybridization. Whole- and core-genome phylogenomic analyses were also carried out. These results were compared with the topologies of the 16S rRNA and gyrB gene phylogenies. Good correlation was found between all trees except for the 16S rRNA gene. Overall results also supported the current classification of M. saelicesensis and M. noduli as separate species. Especially useful was the core-genome phylogenetic analyses based on 92 genes and the dDDH results which were highly correlated. The importance of using more than one strain for a better definition of a species was also shown. A series of in-vitro phenotypic assays performed at different times were compared with in-silico predictions based on genomic data. In-vitro phenotypic tests showed discrepancies among the independent studies, confirming the lack of reproducibility even when tests were performed in the same laboratory. On the other hand, the use of in-silico predictions proved useful for defining a stable phenotype profile among the strains analyzed. These results provide a working framework for defining Micromonospora species at the genomic and phenotypic level.